Transforming Conflicts in Catastrophe, Disaster and Emergency Management (CDEM): The Development of a CDEM Conflict Transformation Platform - Storm, Sarah A. I. (Université Saint-Paul / Saint Paul University, 2012)
Conflict transformation and catastrophe, disaster and emergency management both work toward the mitigation of a crisis. Lederach’s conflict transformation theory provides the basis for a platform that employs conflict transformation concepts and processes to the phases of Catastrophe, Disaster and Emergency Management (CDEM): management, mitigation, preparedness, response and recovery. The CDEM Conflict Transformation Platform was established by synthesizing elements of conflict transformation from the complete works of Lederach and organizing them according to the dominant CDEM framework in North America. It was used to analyze the mitigation, preparedness, response and recovery of Hurricane Katrina in New Orleans from a conflict transformation perspective to gain insights into how it could be applied to address some of the challenges faced due to conflict and latent conflict within the North American CDEM process. The purpose of the CDEM Conflict Transformation Platform is to present an approach to managing conflict within CDEM in North America, which can be used by community members, CDEM professionals, such as city emergency management planners and first responders.
Keywords: Jean Paul Lederach; Conflict Transformation; Emergency Management; Disaster Management; Catastrophe; Mitigation; Hurricane Katrina; New Orleans; Public Safety Canada; Canada; United States; Resilience; Vulnerability; Preparation; Response; Recovery